Implementasi Keselamatan dan Kesehatan Kerja (K3) di Perusahaan Manufaktur Makanan : Studi Kasus pada PT XY - Cece Cece (Jurnal Visi Manajemen, 2026)
Occupational Safety and Health (OHS) is a fundamental aspect in maintaining the smooth production process while maintaining the welfare of workers in the food manufacturing industry. This study aims to analyze in depth the implementation of the OHS program at PT XY, a medium-scale food manufacturing company, by reviewing the applicable policies, program implementation, obstacles encountered, and potential strategies for improvement. The study used a qualitative descriptive approach through direct observation in the production area, semi-structured interviews with 12 informants consisting of managers, supervisors, and operators, and a review of various internal company documents related to OHS. The research findings revealed that the company has a formally formulated OHS policy supported by regular training, but its implementation is not evenly distributed across all work units. Key weaknesses include inconsistent internal audit implementation, low worker awareness in reporting incidents, and a limited number of human resources with specific OHS competencies. Based on these findings, the study recommends strengthening the risk-based OHS management system, increasing human resource capacity, and integrating OHS indicators into the production performance evaluation system to support more optimal OHS implementation in the company.